2018
DOI: 10.1055/s-0038-1646952
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide and Diphenhydramine: A Randomized Controlled Trial of a Treatment for Headache in Pregnancy when Acetaminophen Alone Is Ineffective (MAD Headache Study)

Abstract: MAD effectively relieves headaches in pregnant women when acetaminophen fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…9 One evaluated nonpharmacologic treatment (lifestyle modification) of headache in pregnancy; another assessed acupuncture for women with tension-type headache; and the third evaluated metoclopramide 10 mg intravenously with diphenhydramine 25 mg intravenously compared with codeine 30 mg orally in normotensive patients in the second or third trimester with primary headache. 3,25,26 Prior studies evaluating occipital nerve block in pregnancy focused primarily on treatment of postdural headache. 27,28 One retrospective study evaluated occipital nerve block for refractory migraine and demonstrated that occipital nerve block was effective and did not mask a diagnosis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…9 One evaluated nonpharmacologic treatment (lifestyle modification) of headache in pregnancy; another assessed acupuncture for women with tension-type headache; and the third evaluated metoclopramide 10 mg intravenously with diphenhydramine 25 mg intravenously compared with codeine 30 mg orally in normotensive patients in the second or third trimester with primary headache. 3,25,26 Prior studies evaluating occipital nerve block in pregnancy focused primarily on treatment of postdural headache. 27,28 One retrospective study evaluated occipital nerve block for refractory migraine and demonstrated that occipital nerve block was effective and did not mask a diagnosis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%